HUMAN-PATHOGENIC PARASITES AND BACTERIA LOCATE IN STAGNANT-WATER DURING EL NIÑO-COSTERO PHENOMENON IN PERU - Moya-Salazar, Jeel (2021)
Several countries are extremely susceptible to climate change and the El Niño-costero phenomenon affected more than two million people in Ecuador, Colombia, and Peru. We aimed to evaluate the microbiological quality of stagnant waters in Lambayeque region, Peru during the lockdown caused by El Niño-costero phenomenon. We conducted a cross-sectional study performed in the four Lambayeque’s districts: (Chiclayo’s downtown, Mocupe, San José, and Pimentel), Perú. Two simultaneous samples were taken from each evaluation districts and were transported to Laboratory for their entire microbiological analysis. We isolate of human-pathogenic parasite (Trichuris trichiura (Linnaeus, 1771) and Entamoeba histolytica Schaudinn, 1903), and bacteria (Staphylococcus aureus Rosenbach 1884 and Salmonella typhi (Schroeter, 1886)) that showed patterns of resistance to conventional first-line antimicrobials (penicillin, nalidixic acid, nitrofurantoin, and chloramphenicol). Likewise, we showed evidence of microorganisms related to the sampling site (district) and with the degree of affectation by the phenomenon. Our result suggests that the stagnant waters of four districts of Lambayeque presented Human-pathogenic parasites and bacteria of high-medical importance by the sudden changes in the climate through El Niño-costero phenomenon.